Ethmoidal dural arteriovenous fistula with unusual drainage route treated by transarterial embolization. (25th March 2014) - Inoue, Akihiro; Tagawa, Masahiko; Kumon, Yoshiaki; Watanabe, Hideaki; Shoda, Daisuke; Sugiu, Kenji; Ohnishi, Takanori
Abstract : Ethmoidal dural arteriovenous fistulas (AVFs) are rare intracranial lesions associated with a high risk of intracranial hemorrhage. In particular, this entity with reflux drainage directly into the ophthalmic vein is extremely rare. We report a case of ethmoidal dural AVF with direct drainage of the superior ophthalmic vein (SOV) and inferior ophthalmic vein (IOV), successfully treated by endovascular surgery. A 58-year-old man presented with progressive diplopia. Angiography and contrast-enhanced CT showed an ethmoidal dural AVF supplied via the bilateral anterior ethmoidal arteries and venous drainage through the left SOV and IOV. A transarterial approach through the bilateral anterior ethmoidal arteries was used to place the microcatheter close to the fistula site. After intra-arterial embolization with 20% N-butyl cyanoacrylate, the dural AVF was completely occluded. In patients with good vascular access, endovascular transarterial embolization may be an effective and less invasive treatment strategy for ethmoidal dural AVF.